2016
DOI: 10.1002/med.21424
|View full text |Cite
|
Sign up to set email alerts
|

Nonsteroidal Anti‐Inflammatory Therapy: A Journey Toward Safety

Abstract: The efficacy of nonsteroidal anti-inflammatory drugs (NSAIDs) against inflammation, pain, and fever has been supporting their worldwide use in the treatment of painful conditions and chronic inflammatory diseases until today. However, the long-term therapy with NSAIDs was soon associated with high incidences of adverse events in the gastrointestinal tract. Therefore, the search for novel drugs with improved safety has begun with COX-2 selective inhibitors (coxibs) being straightaway developed and commercialize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
1
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(63 citation statements)
references
References 480 publications
(642 reference statements)
1
59
1
2
Order By: Relevance
“…Cyclooxygenase (COX), lipoxygenase (LOX), and cytochrome P450 (CYP) 4A mainly metabolized arachidonic acid (AA) to prostaglandin E 2 (PGE 2 ), leukotriene B 4 (LTB 4 ), and 20‐hydroxyeicosatetraenoic acid (20‐HETE), respectively . These eicosanoids are key proinflammatory mediators of the inflammatory cascade . PGE 2 and LTB 4 contribute to IL‐1β production, and are thought to be important mediators in gout attack .…”
Section: Introductionmentioning
confidence: 99%
“…Cyclooxygenase (COX), lipoxygenase (LOX), and cytochrome P450 (CYP) 4A mainly metabolized arachidonic acid (AA) to prostaglandin E 2 (PGE 2 ), leukotriene B 4 (LTB 4 ), and 20‐hydroxyeicosatetraenoic acid (20‐HETE), respectively . These eicosanoids are key proinflammatory mediators of the inflammatory cascade . PGE 2 and LTB 4 contribute to IL‐1β production, and are thought to be important mediators in gout attack .…”
Section: Introductionmentioning
confidence: 99%
“…NO‐releasing aspirin is another ester derivative of aspirin. NO is an endogenous gasotransmitter that is involved in various physiological processes including protection of gastrointestinal integrity and cardiovascular system . NO‐aspirin is synthesized by covalent linking aspirin to a spacer that, in turn, is associated with a NO‐releasing moiety .…”
Section: Novel Derivatives Of Aspirinmentioning
confidence: 99%
“…NO is an endogenous gasotransmitter that is involved in various physiological processes including protection of gastrointestinal integrity and cardiovascular system . NO‐aspirin is synthesized by covalent linking aspirin to a spacer that, in turn, is associated with a NO‐releasing moiety . Upon releasing from the aspirin prodrug, NO is able to prevent gastric mucosa damage by increasing mucous secretion, mucosal hemodynamics, and reducing aggregation of neutrophils to gastric mucosa .…”
Section: Novel Derivatives Of Aspirinmentioning
confidence: 99%
“…Phosphatidylcholine was conjugated with NSAIDs to improve the GI safety, and chemical moieties that release protective mediators such as nitric oxide was structurally linked to NSAIDs to attenuate GI and cardiovascular toxicities, and this area of research has shown some promise. 70 …”
Section: Commentmentioning
confidence: 99%